Investigating the causal relationship between energy consumption and firm growth in India. (2015) - Prasad, Mousami; Mishra, Trupti
Energy management is becoming a focus area for corporations to operate sustainably as well as for governments to reduce greenhouse gas emissions. This study investigates the causal relationship between energy consumption and firm growth by applying a panel cointegration technique and vector error correction model. The following four hypotheses have been tested to study this relationship: growth, conservation, feedback and neutrality. Institutional theory and resource-based theory have been used to analyse the results. The sample consists of companies from the metals sector listed on the Bombay Stock Exchange, India. The presence of a bidirectional relationship supports the feedback hypothesis and indicates that any policy aimed at reducing energy consumption affects firm's growth (sales) and vice versa. Additionally, the elasticity of sales with respect to energy is lower than the elasticity of energy with respect to sales.